Auditing and assurance services - Louwers, Timothy J. (McGraw-Hill, 2011)
An auditing text that incorporates professional standards through SAS 116, AS7, international standards of auditing (ISAs), and unnumbered standards adopted through July 2009. It includes chapters that focus on the auditing process